Move for Change Part III: a European survey evaluating the impact of the EPDA Charter for People with Parkinson's Disease. (8th September 2014) - Bloem, B. R.; Stocchi, F.
<x xml:space="preserve">Abstract</x> Background and purpose Move for Change is an online pan‐European patient survey based on the European Parkinson's Disease Association (EPDA) Charter for People with Parkinson's Disease (PD), which states that all PD patients have the right to: be referred to a doctor with a specialist interest in PD; receive an accurate diagnosis; have access to support services; receive continuous care; and take part in managing their illness. Methods This part of the survey focuses on the final two elements of the Charter. It was administered online through the EPDA website and through affiliated patient associations' websites. A total of 1591 questionnaires were received and 1546 were analysed (97.2%). Results Approximately half of the patients (53.0%) consulted a neurologist regularly (every 4–6 months). Consultations were usually arranged as part of a follow‐up process (65.5%) and lasted for 15–30 min (63.2%), with 16.1% lasting <10 min and 17.9% lasting >30 min. Patients were largely satisfied with the attention they received (63.2%) but just 11.6% of patients were involved in treatment decisions, and 39.1% prepared a list of symptom changes for discussion. Two hundred caregivers also took part in the survey, and 71.4% felt included in the treatment plan by the doctor. Conclusions These results highlight that PD disease‐management is driven by the clinician; he/she arranges consultations and makes the majority of management decisions, rather than patients being included in the process. This survey can be used to raise awareness for PD patients, encouraging greater involvement in the management of PD.